Pendampingan Pembentukan Unit Usaha Sarana Produksi (SAPRODI) Pertanian BUMDes Jayan Mandiri dalam Upaya Peningkatan Kesejahteraan Masyarakat Desa Kelubir, Kalimantan Utara - Aksan Halim, K. Prihartono; Abdussalaam, Falaah; Handari Adji, Widwi; Rosmayati, Siti; Paryanti, Dini; Deo Ginoki, Algin; Fery Maulana, Syaifudin; Trimawan, Anang; Wahyudi (LPPM Politeknik Piksi Ganesha, 2024)
Kelubir Village is located in Tanjung Palas Utara Sub-district, Bulungan Regency, North Kalimantan Province which is famous for its corn farming, and is one of the villages that produces the most corn in the North Kalimantan region. According to the Regent of Bulungan, Mr. Syarwani, with the potential plantation area in Kelubir reaching 300 hectares (ha), this can be a hope in improving welfare and supporting food security programs in the region. In addition to corn farming, Kelubir Village also cultivates cocoa plants which is one of the community empowerment assistance programs from PT Pesona Khatulistiwa Nusantara (PKN) Company. In an effort to implement the Tri Dharma of Higher Education, Piksi Ganesha Polytechnic in synergy with PT Pesona Khatulistiwa Nusantara (PKN) and the Bulungan Regency Government, carried out community service activities to encourage the Kelubir Village government to have local revenue through assistance in the formation of a Business Unit under the auspices of the Jayan Mandiri Village-Owned Business Entity (BUMDes), Kelubir Village, North Kalimantan, where the business unit to be run is the Agricultural Production Facilities (Saprodi) business in accordance with the original potential of Kelubir Village, where the majority of the people are farmers. This service uses a participatory method that directly involves the Kelubir Village Government, including the Village Head, BUMDes management and the surrounding community. This community service activity has a positive impact in helping the farmers meet agricultural needs such as fertilizers, seeds, and medicines, which previously had to be reached within 15 km, to 1 km, saving time and transportation costs, increasing productivity and improving the local economy by opening new jobs and encouraging the growth of other businesses around the agricultural area.